Evaluasi Proses Optimalisasi Sumber Daya dan Kegiatan Operasional pada PT. Garuda Maintenance Facility Aeroasia Tbk Menggunakan Kerangka Kerja COBIT 5 Domain EDM 04, APO 07, dan DSS 01 - Bunga Asmara; Yusi Tyroni Mursityo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
PT. GMF Aeroasia Tbk is a company that provides maintenance and repairment services for airline companies. PT. GMF Aeroasia Tbk has a big scope of work and business process, so in this case the company needs an IT Governance that supports the company to achieve company goals. There are many lacking process in PT. GMF Aeroasia Tbk which the company should improve and these are IT assets governance, human resource management which supports the IT operation, and company operational management. With the lacking process, the writer try to have a research for analyzing the capability level with COBIT 5 framework sub domain EDM 04 (Ensure Resource Optimisation), APO 07 (Manage Human Resource), and DSS 01 (Manage Operation). In this research, Data collection is done by an interview, assessment paper questionnaire, and observation. The respondents are EVP Information, Communication & Technology, GM Network & IT Infrastructure, and GM IT Operations which determined by the RACI Chart. The Capability Level achieved by PT. GMF Aeroasia Tbk is Level 3 on EMD 04 sub domain and APO 07, and Level 2 on DSS 01 sub domain. The recommendations that given to PT. GMF Aeroasia Tbk focused on detailing the procedure, established control limit, contract personnel procedure, and process performance measurement.